A Symphytum officinale Root Extract Exerts Anti-inflammatory Properties by Affecting Two Distinct Steps of NF-κB Signaling - Seigner, Jacqueline; Junker-Samek, Marc; Plaza, Alberto; D‘Urso, Gilda; Masullo, Milena; Piacente, Sonia; Holper-Schichl, Yvonne M.; de Martin, Rainer (Frontiers in Pharmacology, 2019)
S. officinale constitutes a traditional medicinal plant with a long-standing therapeutic history, and preparations thereof have been widely used for the treatment of painful muscle and joint complaints, wound and bone healing, and inflammation. Today, its topical use is based on its analgesic and anti-inflammatory effects, which have been substantiated by modern clinical trials. However, the molecular basis of its action remained elusive. Here, we show that a hydroalcoholic extract of comfrey root impairs the development of a pro-inflammatory scenario in primary human endothelial cells in a dose-dependent manner. The extract, and especially its mucilage-depleted fraction, impair the IL-1 induced expression of pro-inflammatory markers including E-selectin, VCAM1, ICAM1 and COX-2. Both preparations inhibit the activation of NF-kappaB, a transcription factor of central importance for the expression of these and other pro-inflammatory genes. Furthermore, our biochemical studies provide evidence that comfrey inhibits NF-kappaB signaling at two stages: it dampens not only the activation of IKK1/2 and the subsequent IkappBalpha degradation, but also interferes with NF-kappaB p65 nucleo-cytoplasmatic shuttling and transactivation. These results provide a first mechanistic insight into the mode of action of a century-old popular herbal medicine.